Hubungan Personal Hygiene terhadap Insiden Pruritus Vulvae pada Remaja Putri di Wilayah Kerja Puskesmas Mijen Kota Semarang - Aura Salsabila Wahyu Trisnian; Hernandia Distinarista; Apriliani Yuliani W; Sri Wahyuni (Journal of Medical Practice and Research, 2026)
Adolescence is an important period in the development of reproductive health, particularly for adolescent girls who have experienced menstruation, as inadequate personal hygiene in the genital area can increase the risk of pruritus vulvae, which is characterized by itching and discomfort. This study aimed to determine the relationship between personal hygiene and the incidence of pruritus vulvae among adolescent girls in the working area of Mijen Public Health Center, Semarang City. This study employed a quantitative method with a cross-sectional design involving 109 adolescent girls who had experienced menstruation and were unmarried, selected using a consecutive sampling technique. Data were collected using personal hygiene and pruritus vulvae questionnaires and analyzed using the Spearman Rank correlation test with a significance level of α = 0.05. The results showed that most respondents had good personal hygiene (74.3%) and the majority did not experience pruritus vulvae (53.2%). Statistical analysis revealed a significant and strong relationship between personal hygiene and pruritus vulvae (p = 0.000; r = -0.502), indicating that better personal hygiene is associated with a lower incidence of pruritus vulvae. In conclusion, personal hygiene is significantly associated with the occurrence of pruritus vulvae among adolescent girls in the working area of Mijen Public Health Center, Semarang City.